Shexiang Tongxin Dropping Pills Promote Macrophage Polarization-Induced Angiogenesis Against Coronary Microvascular Dysfunction via PI3K/Akt/mTORC1 Pathway - Xiangyu Lu; Junkai Yao; Changxiang Li; Lingwen Cui; Yizhou Liu; Xiangning Liu; Gang Wang; Jianteng Dong; Qiong Deng; Yueyao Hu; Dongqing Guo; Wei Wang; et al. (Frontiers Media S.A., 2022)
Background: Accumulating evidence suggests that coronary microvascular dysfunction (CMD) is one of the important causes of coronary artery diseases. Angiogenesis can effectively improve CMD by increasing blood supply capacity, recovering cardiac function and poor hemodynamics. Clinical studies have approved Shexiang Tongxin dropping pill (STDP), which has exerted remarkable roles on ameliorating CMD, but the effects and mechanisms of STDPs on angiogenesis have not been clarified.Purpose: The purpose of this study was to elucidate the effects and potential mechanisms of STDPs on macrophage polarization-induced angiogenesis against CMD.Methods: Echocardiography, optical microangiography (OMAG), and histological examination were applied to evaluate cardioprotection and proangiogenic effects of STDPs on left anterior descending (LAD) ligation-induced CMD rats. In vitro, oxygen-glucose deprivation-reperfusion (OGD/R)-induced HUVEC model and LPS-stimulated bone marrow-derived macrophage (BMDM) model were established to observe the effects of STDPs on angiogenesis and M2 macrophage polarization.Results: STDPs improved cardiac function, increased microvascular density, and the number of M2 macrophages in the heart of CMD rats. In vitro, STDPs accelerated the proliferation, migration, and tube formation in OGD/R-induced HUVECs similar to the effects of VEGF-A. Furthermore, in LPS-stimulated BMDMs model, STDPs modulated M2 macrophage polarization and increased VEGF-A release via the PI3K/AKT/mTORC1 pathway.Conclusion: STDPs promoted macrophage polarization-induced angiogenesis against CMD via the PI3K/Akt/mTORC1 pathway. Our results demonstrated that the phenotype transformation of macrophages and stimulating the secretion of VEGF-A may be applied as novel cardioprotective targets for the treatment of CMD.